2016
DOI: 10.4172/2329-8847.1000159
|View full text |Cite
|
Sign up to set email alerts
|

Adding A Dietician to the Liaison-Team after Discharge of Geriatric Patients at Nutritional Risk May Save Health Care Costs

Abstract: Adding a Dietitian to a Danish Liaison-Team after discharge of geriatric patients at nutritional risk may save health care costs. Aging Sci 4: 159.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…At Herlev Gentofte Hospital and other Danish hospitals, several randomized controlled nutritional intervention studies have aimed at solving the nutritional gap ( [1,2,6,9,14,24,25,27]). These studies have provided individualized dietary counseling, including ONSs if found necessary, but without any provision of food.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At Herlev Gentofte Hospital and other Danish hospitals, several randomized controlled nutritional intervention studies have aimed at solving the nutritional gap ( [1,2,6,9,14,24,25,27]). These studies have provided individualized dietary counseling, including ONSs if found necessary, but without any provision of food.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have provided individualized dietary counseling, including ONSs if found necessary, but without any provision of food. Even though all these studies have found positive effects on dietary intake and/or nutritional status, the beneficial effect on patient-relevant outcome measures (PROMs), such as quality of life and readmissions, has been very limited ( [1,2,6,9,14,24,25,27]). This is confirmed by systematic reviews conducted in the field [5,16,19,28].…”
Section: Introductionmentioning
confidence: 99%
“…Using data from a dietician to a geriatric discharge Liaison-Team, this study is carried out to explore the possible economic savings of Health care costs. Authors Anne et al [2], observed a cost saving of approximately 3,000 euro for each patient receiving nutritional support during six months after discharge from hospital. However, this study is not designed as a cost study and the costs associated with them are estimated, both in terms of quantity and the actual expenses.…”
mentioning
confidence: 99%